Effect of processing on the antioxidant activity of cassava (Manihot Esculenta Crantz) - Pacariem, Kristoffer Talla
ABSTRACT This study aimed to determine the effect of boiling and tapioca pearl processing on the total phenolic content and antioxidant activity of the methanolic extracts of cassava (Manihot esculenta Crantz) tubers. Total phenolic content of the methanolic extracts of cassava was determined through the Folin-Ciocalteau method. Antioxidant properties such as the DPPH free radical scavenging activity, reducing power, ferrous-ion chelating capacity and total antioxidant activity through the ferric-thiocyanate assay of the methanolic extracts of cassava were also determined. Total phenolic content of the methanolic extracts of cassava ranged from 5.737 to 10.696 mg GAE/100 g dry matter. Total phenolic content has a strong correlation with ferrous-ion chelating capacity (r=0.702) but has a weak correlation with the total antioxidant activity, reducing power and DPPH radical scavenging ability. Processing methods applied had no significant (P>0.05) effect on the total phenolic content. On the other hand, varying effects were observed on the antioxidant properties of cassava after subjecting it to different processing treatments. Reducing power, DPPH radical scavenging activity, ferrous-ion chelating capacity and total antioxidant activity of steamed cassava, boiled cassava and tapioca pearl were significantly different (P<0.05). The total antioxidant activity, DPPH radical scavenging activity and reducing power of the cassava extracts were found to be weaker than that of alpha-tocopherol. However, the metal ion chelating capacity of the cassava extracts was higher than that of EDTA. Results from this study indicate that cassava tuber can be a potent source of natural antioxidants.